The Role Of Arabic Language And Its Impact In Improving Education Among Children - Hanan Sa’di Mahmud; Zahro' Humaid Mageed; Noor Khalid Muhyiddn (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The research dealt with an important topic that is related to humanity in general and children In particular, it is the role of knowing the Arabic language in increasing the linguistic perception of children because they are like a seed. In growing up, their tongues must be straightened in a way that increases their linguistic balance, because of the importance of acquiring wealth Linguistic makes him recognize all literary and non-literary texts, relie in this study onThe effect of stories on linguistic behavior and the importance of children's knowledge of language in simplified and smooth ways Including stories and tales, and stories are considered a means of desire to increase linguistic wealth In addition to the growth of cognitive stimulation and the development of their knowledge of the originality of the Arabic language and literature in a way Special, and add to that also that the child becomes more familiar with the Arab culture and has a queen Artistic taste for intellectual output.